Liposomes with pH responsive 'on and off' switches for targeted and intracellular delivery of antibiotics. (2nd January 2021) - Omolo, Calvin A.; Megrab, Nagia A.; Kalhapure, Rahul S.; Agrawal, Nikhil; Jadhav, Mahantesh; Mocktar, Chunderika; Rambharose, Sanjeev; Maduray, Kaminee; Nkambule, Bongani; Govender, Thirumala
Abstract: pH responsive drug delivery systems are one of the new strategies to address the spread of bacterial resistance to currently used antibiotics. The aim of this study was to formulate liposomes with 'On' and 'Off'' pH responsive switches for infection site targeting. The vancomycin (VCM) loaded liposomes had sizes below 100 nm, at pH 7.4. The QL-liposomes had a negative zeta potential at pH 7.4 that switched to a positive charge at acidic pH. VCM release from the liposome was quicker at pH 6 than pH 7.4. The OA-QL-liposome showed 4-fold lower MIC at pH 7.4 and 8- and 16-fold lower at pH 6.0 against both MSSA and MRSA compared to the bare drug. OA-QL liposome had a 1266.67- and 704.33-fold reduction in the intracellular infection for TPH-1 macrophage and HEK293 cells respectively. In vivo studies showed that the amount of MRSA recovered from mice treated with formulations was 189.67 and 6.33-fold lower than the untreated and bare VCM treated mice respectively. MD simulation of the QL lipid with the phosphatidylcholine membrane (POPC) showed spontaneous binding of the lipid to the bilayer membrane both electrostatic and Van der Waals interactions contributed to the binding. These studies demonstrated that the 'On' and 'Off' pH responsive liposomes enhanced the activity targeted and intracellular delivery VCM.